2D Covalent Organic Frameworks for Biomedical Applications. (29th April 2020) - Bhunia, Sukanya; Deo, Kaivalya A.; Gaharwar, Akhilesh K.
Abstract: Covalent organic frameworks (COFs) are an emerging class of organic crystalline polymers with well‐defined molecular geometry and tunable porosity. COFs are formed via reversible condensation of lightweight molecular building blocks, which dictate its geometry in two or three dimensions. Among COFs, 2D COFs have garnered special attention due to their unique structure composed of two‐dimensionally extended organic sheets stacked in layers generating periodic columnar π‐arrays, functional pore space, and their ease of synthesis. These unique features in combination with their low density, high crystallinity, large surface area, and biodegradability have made them an excellent candidate for a plethora of applications ranging from energy to biomedical sciences. In this article, the evolution of 2D COFs is briefly discussed in terms of different types of chemical linkages, synthetic strategies of bulk and nanoscale 2D COFs, and their tunability from a biomedical perspective. Next, the biomedical applications of 2D COFs specifically for drug delivery, phototherapy, biosensing, bioimaging, biocatalysis, and antibacterial activity are summarized. In addition, current challenges and emerging approaches in designing 2D COFs for advanced biomedical applications are discussed. Abstract : Covalent organic frameworks (COFs) are an emerging class of organic crystalline polymers with well‐defined molecular geometry and tunable porosity. This review discusses recent advances in the field of 2D COFs for biomedical applications.